Preparation of octenylsuccinic anhydride modified starches and their applications in emulsion and encapsulation - Sun, Zhenhua (Kansas State University, 2020)
Starches esterified with octenylsuccinic anhydride (OSA) are lipophilic and have been used as emulsion stabilizers in beverage, food, pharmaceutical and personal care applications. The traditional method for synthesizing octenylsuccinate (OS) starch is to react granular starch with OSA in an aqueous slurry system under mild alkaline conditions. In this dissertation, distribution of OS substituents within a single granule of modified maize and potato starches was investigated, and new technologies developed in our laboratory were used to prepare OS starches for emulsion and encapsulation applications. OS distribution predominantly occurred on the surface of the waxy maize starch granules as determined by Raman microspectroscopy, and the level of OS substitutes in the center of granules was also high and nearly equal to that on the surface. The regions between the surface and the hilum of the waxy maize starch granules had reduced OS substitution. In contrast, OS groups in OSA-modified waxy and normal potato granular starches were shown to be preferentially located on its surface. The DS of granule ghosts (the remnant of starch granule after cooking under low shear) suggested that the OS groups on the surface was about 2.5 times that of the bulk after 60% interior granule was lost and removed. In beverage application, OS waxy potato starch, which has excellent paste clarity, was hydrolyzed by α-amylase, and the products displayed good emulsion stability for orange oil. Compared with the aqueous slurry system, the dry heating treatment for synthesizing OS starch appeared simpler, and more economical with higher yield. The OS waxy maize starch prepared by dry heating treatment was used to emulsify and encapsulate vitamin E. The stability of encapsulated vitamin E (VE) particles was excellent by OSA-modified normal maize starch prepared by dry heating method. Fresh emulsions with the high ratio of starch to VE (1:1) had a small particle size of 0.7 μm. The conformational properties of starch granules during dextrinization (dry heating in the presence of acid) were investigated by high performance size exclusion chromatography (HPSEC) coupled with multiple detectors. The measured exponent α values in Mark-Houwink equation indicated that pyrodextrins prepared at pH 3, 170 °C and 150 °C only had one compact spherical conformation (α 0.27-0.31) during dextrinization, whereas pyrodextrins at pH 2 and 150 °C had a mixture of two shapes of molecules: compact sphere (α 0.26) and rigid coil (α 0.89) conformation. Pyrodextrins prepared at pH 3 and 150 °C for 4 h and its swollen granules recovered from glycerol/water mixtures were determined by X-ray diffraction and DSC, and the results showed that short-range crystallinity was destroyed but long-range order (birefringence) was retained. Interestingly, some intact granules could swell as much as 80% in glycerol/water 40/60 to 60/40 at 10% starch solids and still displayed Maltese cross patterns, but were not crystalline.
Keywords: Octenylsuccinic anhydride; Modified starches; Emulsion; Encapsulation; Pyrodextrin